2022
DOI: 10.37934/cfdl.14.3.2238
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Mixed Convection and Radiative Al2O3-Cu/H2O Hybrid Nanofluid Flow over a Vertical Exponentially Shrinking Sheet with Partial Slip Conditions

Abstract: Hybrid nanofluid is considered a modern and improvised form of nanofluid which usually used to enhance the performance of heat transfer in fluid flow systems. Previous studies found hybrid nanofluid offered a wide range of applications and this opened up numerous new opportunities to further explore the unknown behaviour of hybrid nanofluid under different body geometries and physical parameters. This paper numerically studied a two-dimensional mixed convection and radiative Al2O3-Cu/H2O hybrid nanofluid flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…An analysis of stability revealed that the upper (first) solution was stable, while the lower (second) solution was unstable. Asghar et al, [28] investigated an exponentially contracting vertical surface in mixed convection flow under slip conditions and radiation effects. To solve numerically, they used the bvp4c function in MATLAB.…”
Section: Magnetic Field Bvp4cmentioning
confidence: 99%

Exploration of Recent Developments of Hybrid Nanofluids

Nur Syahidah Nordin,
Abdul Rahman Mohd Kasim,
Masyfu’ah Mokhtar
et al. 2024
ARFMTS
“…An analysis of stability revealed that the upper (first) solution was stable, while the lower (second) solution was unstable. Asghar et al, [28] investigated an exponentially contracting vertical surface in mixed convection flow under slip conditions and radiation effects. To solve numerically, they used the bvp4c function in MATLAB.…”
Section: Magnetic Field Bvp4cmentioning
confidence: 99%

Exploration of Recent Developments of Hybrid Nanofluids

Nur Syahidah Nordin,
Abdul Rahman Mohd Kasim,
Masyfu’ah Mokhtar
et al. 2024
ARFMTS
“…However, due to their own advantages and disadvantages, hybrid nanofluids came into existence and may offer a tradeoff between them. For instance, Asghar et al [21] performed a numerical study on the impact of hybrid nanofluid (Al2O3-Cu base) over vertical shrinking sheets using partial slip conditions. From this study, the enhancement in heat transfer was observed along with the rise in thermal slip and temperature distribution.…”
Section: Greek Symbolsmentioning
confidence: 99%
“…Eid and Nafe [17] noted that the thermal slip parameter affects the flow over the stretching sheet differently from the shrinking sheet. Besides that, many researchers have studied hybrid nanofluid flow with slip boundary conditions [18][19][20][21][22]. However, most of these studies did not consider the effects of mass slip on the hybrid nanofluid flow.…”
Section: Introductionmentioning
confidence: 99%